Timestamp-Based Algorithms for Concurrency Control in Distributed Database Systems - Bernstein, Phil; Goodman, Nathan (International Conference on Very Large Data Bases, 1980)
We decompose the problem of concurrency control into the sub-problems of read-write and write-write synchronization. We present a series of timestamp-based algorithms (called synchronization techniques) that achieve read-write and/or write-write synchronization. And we show how to combine any read-write technique with any write-write technique to yield a complete concurrency control algorithm (called a method). Using this framework we describe 12 “principal” concurrency control methods in detail. Each principal method can be modified by refinements described in the paper, leading to more than 50 distinct concurrency control algorithms.